Título Padrão - Figueiredo, Judah; Vieira, David Vernon (Informação em Pauta, 2022)
Presents the strategic planning of marketing in libraries. Discusses the application of SWOT analysis in Libraries. It carries out a SWOT analysis of the strengths and weaknesses, threats and opportunities, in the external and internal aspects of the Library of the Federal Institute of Ceará, Crato campus., Suggest a marketing plan containing actions that improve the library's visibility. The research approach is applied, with the analysis of data in a qualitative way. The method is characterized as exploratory and descriptive and bibliographical in nature. It was found that the difficulties faced are concentrated in the financial sphere that directly impact the development of activities, the dissemination of actions and interaction with users. In the face of uncertainty and scarcity of budget resources, the creation of profiles on social media and marketing actions that improve communication and dissemination of library services and products with the user community is suggested.